Chapter New Scenarios for a Development between Infrastructures and Innovation - Savron, Matteo (Proceedings e report, 2020)
Both infrastructure and research, make communications and exchanges between distant places possible. As a consequence, geographic positions and administrative borders are less and less significant compared to the polarity of the individual cities. From the port and infrastructural systems' point of view, Trieste, can closely resemble this model by strengthening the two drivers for development, quality of life and employment opportunity. The specificity that needs to be investigated is the complex system that joins port logistics with innovation promoted by AREA Science Park among others.